Gender and sex in the development and progression of renal diseases - Marcora Mandreoli (AboutScience Srl, 2023)
Sex-based disparities in nephrology have been a historically understudied area. In nephrology, gender differences exist with regard to the epidemiology, evolution and prognosis of chronic kidney disease (CKD). In some cases, these differences run contrary to the general population trends. We discuss such gender and sex disparities, including differing impact of traditional and novel risk factors, as well as hormonal factors, all of them potentially influencing propensity, progression and biochemical and psychological aspects of CKD. The factors involved in this gender disparity may include diet, kidney and glomerular size, differences in glomerular hemodynamics, and the direct effects of sex hormones. The progression rate of many renal diseases is affected by sex. In polycystic kidney disease, membranous nephropathy, immunoglobulin A nephropathy, and "chronic renal disease of unknown etiology", men progress at a faster rate to end-stage renal failure than women do. In many, but not all, animal models of renal disease, estrogens slow progression rate. Animal and experimental studies have tried to offer further mechanistic explanations for gender differences in disease progression. It has been suggested that the gender dimorphism of CKD progression may represent the effects of the interaction of circulating steroids with specific kidney receptors. Endogenous estrogens have in general been considered to have anti-fibrotic and anti-apoptotic effects on the kidney. On the other hand, the faster decline of kidney function in men has been attributed to the specific pro-apoptotic and pro-fibrotic properties of androgens.